2015
DOI: 10.1212/wnl.0000000000002015
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in incidence, case fatality, and mortality of intracerebral hemorrhage

Abstract: In the Netherlands, ICH incidence, case fatality, and mortality rates have declined significantly in men and women younger than 75 years but remained stable in patients 75 years and older. The observed time trends may be explained by better prevention and treatment during the previous 2 decades of which the elderly do not seem to benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
78
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 28 publications
6
78
3
1
Order By: Relevance
“…The 48% reduction in the incidence rate of PICH was close to the reduction of over 50% that was found in Oxfordshire, UK . The reported decrease in PICH incidence was evident in both sexes and in all age groups and was remarkable in subjects aged less than 75 years, as observed in other studies . The decrease probably depends on more effective control of risk factors, especially arterial hypertension, and improved diagnosis of secondary ICH.…”
Section: Discussionsupporting
confidence: 84%
“…The 48% reduction in the incidence rate of PICH was close to the reduction of over 50% that was found in Oxfordshire, UK . The reported decrease in PICH incidence was evident in both sexes and in all age groups and was remarkable in subjects aged less than 75 years, as observed in other studies . The decrease probably depends on more effective control of risk factors, especially arterial hypertension, and improved diagnosis of secondary ICH.…”
Section: Discussionsupporting
confidence: 84%
“…Increasing age is also associated with increased morbidity and elderly population above 70 years had a high mortality rate (46.1%) in our series. Several authors have shown that older adults with acute ICH experienced the worse outcomes compared with their younger counterparts, including death, dependency, and overall quality of life [5,[24][25][26].…”
Section: Intraventricular Extension Intraventricular Extensionmentioning
confidence: 99%
“…14,16,17 ICD-9 and ICD-10 codes for the identification of stroke have been proven to be reliable in studies of patients with stroke of all ages. 18,19 For this study, we specifically assessed the accuracy of ICD-10 codes for young adults (aged 18-49 years). We checked final diagnoses in medical records against the attached ICD-10 code at discharge of 569 patients admitted in 2 university medical centers and 1 large general hospital between 1995 and 2017.…”
Section: Exposurementioning
confidence: 99%